THE EFFECT AT MUSCLE POWER ARM, HAND-EYE COORDINATION, FLEXIBILITY AND SELF CONFIDENCE UPON BADMINTON SMASH SKILL - Myrza Akbari; Firmansyah Dlis; Widiastuti Widiastuti (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to reveal whether there is effect muscle power arm, hand eye coordination, flexibility and confidence to smash badminton skills, either directly or indirectly. The research was conducted at the Serambi Mekkah University, with a sample consisting of 73 samples were selected from 677. physical education, health and recreation students, serambi mekkah university of Banda Aceh